Can Vaccinations Improve Heart Failure Outcomes? Contemporary Data and Future Directions - Bhatt, Ankeet S. (JACC Heart Fail, 2017)
Heart failure (HF) is a chronic syndrome characterized by acute exacerbations. There is significant overlap between respiratory infections and exacerbation of underlying HF. Vaccination against respiratory infections in HF patients could serve as a potential cost-effective intervention to improve patients’ quality of life and clinical outcomes. The benefits of influenza vaccination in secondary prevention of ischemic heart disease have been previously studied. However, the evidence for influenza and pneumococcal vaccination specifically in the HF population is less well established. Furthermore, questions around the optimal timing, dose, frequency, and implementation strategies are largely unanswered. This review highlights the current evidence for vaccination against influenza and pneumococcal pneumonia in HF and cardiovascular disease in general. It summarizes current understanding of the pathophysiologic mechanisms in which vaccination may provide cardioprotection. Finally, it offers opportunities for further investigation of the effects of vaccination in the HF population, including basic science, translational research, and large clinical trials.